Self-Rated Health Status and the Risk of Incident Type 2 Diabetes: A Prospective Cohort Study of Middle-Aged and Older Chinese - Lin Wu; Ruyi Chen; Aiping Sheng; Hongqiang Lou; Xiaowen Wang (Frontiers Media S.A., 2024)
ObjectivesEvidence on the relationship between self-rated health status and incident type 2 diabetes (T2DM) in China is scarce. This study aims to examine the prospective association of self-rated health status with the subsequent risk of T2DM among middle-aged and older Chinese subjects.MethodsData were obtained from the China Health and Retirement Longitudinal Study of 9844 Chinese individuals aged 45 years or older. Cox proportional hazards models were used to yield hazard ratios (HRs) relating self-rated health status to the 7-year incidence of T2DM, adjusting for conventional risk factors.ResultsCompared to those with very good or good self-rated health, individuals with poor health had a significantly higher risk of developing T2DM in the multivariable-adjusted model [HR = 1.36 (1.07, 1.73)]. Subgroup analysis by sex showed stronger associations in women [HR = 1.53 (1.11, 2.12)]. Interaction analyses indicated that factors such as age, sex, obesity, smoking status, drinking status, history of hypertension and history of dyslipidemia did not modify the association (all P-interaction >0.05).ConclusionPoor self-rated health status is associated with a higher risk of developing T2DM in middle-aged and older Chinese people.